Matematică
puradel
2015-11-07 08:00:09
Ex 2. Va rog mult. E urgent
Răspunsuri la întrebare
DavidDolha2002
2015-11-07 14:19:49

Am atasat rezolvarea.

Dariiiiiiiii
2015-11-07 14:21:04

a) [latex]it f=x^3-4x^2-x+4 =(x^3-x) -4(x^2-1) = \;\ =x(x^2-1)-4(x^2-1) =(x^2-1)(x-4) (*) \;\ (*) Longrightarrow f:(x^2-1) =x-4 rest 0.[/latex] b) [latex]it f=x^3-4x^2-x+4 \;\ f(x_1) = 0 Rightarrow x_1^3-4x_1^2-x_1+4 =0 Rightarrow x_1^3 = 4x_1^2 + x_1 - 4 (1) \;\ f(x_2) = 0 Rightarrow x_2^3-4x_2^2-x_2+4 =0 Rightarrow x_2^3 = 4x_2^2 + x_2 - 4 (2) [/latex] [latex]it f(x_3) = 0 Rightarrow x_3^3-4x_3^2-x_3+4 =0 Rightarrow x_3^3 = 4x_3^2 + x_3 - 4 (3)[/latex] [latex]it (1),(2), (3)Rightarrow x_1^3+x_2^3+x_3^3 =4(x_1^2+x_2^2+x_3^2)+(x_1+x_2+x_3)-12[/latex] c) [latex]it f=0 stackrel{(*)}{Longrightarrow}(x^2-1)(x-4)=0 egin{cases}it x^2-1=0Rightarrow x^2=1 Rightarrow x=pm1 \;\ it x-4=0 Rightarrow x=4end{cases}[/latex] [latex]it S={-1, 1, 4}[/latex]

Adăugați un răspuns